2022
DOI: 10.1111/srt.13159
|View full text |Cite
|
Sign up to set email alerts
|

Devices measuring transepidermal water loss: A systematic review of measurement properties

Abstract: Objective The objective of this review is to examine the reliability and measurement error of devices that measure transepidermal water loss (TEWL). Introduction TEWL is a physiological property of skin which increases when the epidermis is damaged. It is, therefore, a commonly utilised measure of skin barrier integrity. Devices measuring TEWL are available as open, semi‐open or closed chamber. Studies of reliability examine the consistency of measurement, and/or responsiveness whereas measurement error scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
(313 reference statements)
1
11
0
Order By: Relevance
“…The most expressed functional change in the skin after SVF administration was a decrease in the amount of transepidermal water loss. It is known that TEWL correlates to the greatest extent with the state of the skin surface layer—the epidermis: in the case that its integrity is damaged or it is thinned, water loss increases, while, on the contrary, full epithelialization of the wound surface is followed by a decrease in the level of TEWL ( 45 ). Other authors have described a direct correlation between the state of the newly formed cover tissues and their ability for thermal regulation: the horny layer of epidermal keratinocytes is crucial as a physical barrier ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most expressed functional change in the skin after SVF administration was a decrease in the amount of transepidermal water loss. It is known that TEWL correlates to the greatest extent with the state of the skin surface layer—the epidermis: in the case that its integrity is damaged or it is thinned, water loss increases, while, on the contrary, full epithelialization of the wound surface is followed by a decrease in the level of TEWL ( 45 ). Other authors have described a direct correlation between the state of the newly formed cover tissues and their ability for thermal regulation: the horny layer of epidermal keratinocytes is crucial as a physical barrier ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study did not address barrier alterations and repair dynamics. Repair mechanism and their modulation are known not to be instrument dependent since each volunteer/patient serves as its control 4,11 . Future clinical studies will include the assessment of TEWL values of patients suffering from inflammatory dermatosis with epidermal involvement and the modulation of TEWL values by topical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…mechanism and their known to be instrument dependent since each volunteer/patient serves as its control. 4,11 Future clinical studies will include the assessment of TEWL values of patients suffering from inflammatory dermatosis with epidermal involvement and the modulation of TEWL values by topical treatments. We expect that TM Hex will be used in studies assessing barrier alterations and their treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of experimental devices to study TEWL, including the vapometer used in this study, are well utilized in clinical practice and have been compared by Klotz et al We have identified in Table where equivalent, or alternative, instrumentations have been used to indicate a normal distribution of TEWL against the body site within the literature. Depending on the device used, the exact measured value of a skin site can vary as much as from 2 to 12 g –2 h –1 , but each device is generally internally consistent .…”
Section: Review Of the Stratum Corneum Trans Epidermal Water Loss And...mentioning
confidence: 99%